2018
DOI: 10.1016/j.jaad.2018.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of dermatitis after PD-1/PD-L1 inhibitor therapy and association with multiple oncologic outcomes: A retrospective case-control study

Abstract: Lichenoid and spongiotic dermatitis associated with PD-1/PD-L1 inhibitors could be a sign of robust immune response and improved oncologic outcomes. The value of PD-1/PD-L1-related dermatitis in predicting cancer outcomes awaits investigation through prospective multicenter studies for specific cancer types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
49
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 17 publications
6
49
1
Order By: Relevance
“…In our cohort, longer PFS and OS were found not only in patients who developed vitiligo but also in cases of SE and altogether cutaneous AEs. This was also reported in previous studies and put the skin SE as a predictor of tumour response under anti‐PD‐1 treatment …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In our cohort, longer PFS and OS were found not only in patients who developed vitiligo but also in cases of SE and altogether cutaneous AEs. This was also reported in previous studies and put the skin SE as a predictor of tumour response under anti‐PD‐1 treatment …”
Section: Discussionsupporting
confidence: 82%
“…OS was found to be greater in patients who experienced an AE compared with those who did not, particularly for individuals with 3 and more AEs . In a recent case–control study, the development of dermatitis was found to be associated with longer PFS and OS in cases patients compared to the controls . Dermatitis was 23.25‐fold more frequent in case of cutaneous malignancies compared to lung cancer patients.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Dermatitis has also been associated with improved outcomes. For instance, a retrospective case‐control study that included 20 patients with multiple tumor types who were treated with PD‐1/PD‐L1 blockade and developed biopsy‐proven dermatitis found that patients who developed dermatitis had improved progression‐free and overall survival compared with patients who did not develop dermatitis …”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%
“…The presentation is diverse and includes maculopapular or papulopustular rash, dermal hypersensitivity reaction, dermatomyositis, Sweet syndrome, pyoderma gangrenosum, acute generalized exanthematous pustulosis, acneiform rash, photosensitivity reactions, drug reaction with eosinophilia and systemic symptoms (DRESS), bullous disorders, psoriasis, vitiligo, and regression of melanocytic nevi . The most commonly reported cutaneous toxicities are maculopapular rash, pruritis, and vitiligo .…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%